Efeito de tensões de água no solo na qualidade e longevidade floral do crisântemo de corte - Farias, Marizélia Furtado de; Saad, João Carlos Cury [UNESP]; Carnietto, Mirela [UNESP]; Laschi, Denise [UNESP] (My University, 2010)
The experiment was carried out on the Steltenpool property, in the Holambra II District of the Paranapanema (SP) municipality. e research principal objective was to identify the soil water tension which would result in improved quality and greater longevity for cut chrysanthemums, Dark Orange Reagan cultivar. e treatments were de"ned for ten tension levels: 5, 10, 15, 20, 25, 30, 35, 40, 45 and 50 kPa. In the last evaluation, when the chrysanthemums were showing open +owers, some plants were taken to the FCA/UNESP Department of Horticulture laboratory and submitted to two treatments to maintain longevity. e treatments were: T1, treatment with distilled water; T2, treatment with distilled water + gibberellic acid (GA3 30 mg.L- 1 ). Daily analyses with speci"c formulae were realized, with notes attributed to each plant. ree repetitions for each tension treatment were used, with 30 stems for T1 and 30 for T2, totaling 60 stems. e stems were conditioned in pet bottles "lled with 500 mL of water. e notes were given according to the following criteria: (1) generalized yellowing, soften stems, advanced wilting and discard; (2) onset of yellowing and wilting; (3) onset of falling leaves; (4) some wilted leaves; (5) normal green in+orescent turgid leaves (best quality). e conclusions drawn from the results obtained were that a greater number of A1 packets, of the best quality standard, were found with tensions of 20 and 50 kPa and that greater longevity was achieved using gibberellin (GA3 ) at a concentration of 30 mg.L-1, at tensions of 30 and 50 kPa.

Esta experiencia fue realizada en la propiedad Steltenpool, en el districto de Holambra II municipalidad ParanapanemaSan Pablo – Brasil. Su objetivo fué identi3car la mejor tensión del agua en el suelo que permitiera el desarrollo de plantas de crisantemos de corte de mejor calidad y mayor longevidad – cv Dark Orange Reagan. Los tratamientos fueron de3nidos por diez niveles de tensiones : 5, 10, 15, 20, 25, 30, 35, 40, 45 e 50 kPa. Cuando los crisantemos estaban con sus 6ores abiertas, llevamos algunas plantas al laboratório del Departamento de Horticultura de la Facultad de Ciencias Agronómicas y las submetimos a dos tratamientos de manutención de la longevidad. T1: tratamiento con agua destilada y T2: tratamiento con agua destilada + ácido giberélico (GA3 30 mg.L-1). Fueron realizados analisis diários, con formularios especí3cosatribuyendole nota a cada planta. Realizamos tres repeticiones de la experiencia para cada tratamiento (tensión) de la siguiente forma: 30 hastes para T1 y 30 hastes para T2, totalizando 60 hastes. Cada uno dela hastes fue concicionado en botellas plasticas “pet” conteniendo: 500ml de agua natural. Los mejores resultados se obtuvieron con el empleo de la giberelina en la siguiente proporción: (GA3 ) na concentração de 30 mg.L-1 independientemente de la tensión utilizada.

O experimento foi realizado na propriedade Steltenpool, no Distrito de Holambra II, município de Paranapanema(SP). O objetivo deste estudo foi identi3car a tensão de água no solo que resultasse em uma melhor qualidade e maior longevidade do crisântemo de corte, cv. Dark Orange Reagan. Os tratamentos foram de3nidos por dez níveis de tensão: 5, 10, 15, 20, 25, 30, 35, 40, 45 e 50kPa. Ao 3nal do experimento, quando os crisântemos já estavam com as 6ores abertas, algumas plantas foram levadas para o Laboratório do Departamento de Horticultura, da Faculdade de Ciências Agronômicas, e submetidas a dois tratamentos para a manutenção da longevidade. Os tratamentos foram: T1 - tratamento com água destilada; T2 - tratamento com água destilada + ácido giberélico (GA3 30 mg.L-1). Foram realizadas análises diárias, com formulários especí3cos, atribuindo-se notas para cada planta. Utilizou-se 3 repetições em cada tratamento (tensão), sendo 30 hastes para T1 e 30 hastes para T2, totalizando 60 hastes. As hastes foram acondicionadas em garrafas pet, preenchidas com 500ml de água natural. A melhor qualidade e longevidade 6oral foi obtida com o emprego da giberelina (GA3 ) na concentração de 30mg.L-1, independentemente da tensão usada.
Effect of soil-water tension on cut chrysanthemum floral quality and longevity
Efecto de tensión del agua en el suelo el la calidad y longevidad del crisantemo de corte
Keywords: Dendranthema grandiflorum Ramat; Kitamura; Post-harvest; Irrigation; Dendranthema grandioflorum Ramat; Kitamura; Pós cocecha; Irrigación; Dendranthema grandiflorum Ramat; Kitamura; Pós-colheita; Irrigação